“Ephemeralization” dalam Pelaksanaan Upacara Perkawinan Adat Bali - I Made Adi Surya Pradnya (Universitas Udayana, 2020)
In the last ten years there has been a new phenomenon in the implementation of traditional Balinese wedding ceremonies. This phenomenon in the simplication, the use of agents anda professional staff, so it is called ephemeralitation. This article discusses the forms of thought and the implication of ephemeralization in traditional Balinese wedding ceremonies. Data was collected by interviewing bride and groom, and professionals. Observation was done at Taman Bhuana Prakerti, Beng Village, Gianyar and Muncan Village, Karangasem and social media as wll. Documentations were collected in the form of photos of the ceremony implication and literature study in the form of books. The theory used was ephemeralization thery. As a result of the discussion, ephemeralization thought in Balinese Traditional wedding ceremony were initially rejected, but it was increasingly in demand, because it was more practical, efficient and economical. The form of ephemeralization was in the form of buying ceremonial means and using professional staff. This thought has some implications for reducing the time of ngayah (social service), so that it is more effective and the cost of marriage becoming cheaper.